THE ERROR ANALYSIS REFLECTED IN ENGLISH RECOUNT WRITING - N.W.Y., Megantari; I.G., Budasi (Universitas Pendidikan Ganesha, 2018)
This study was designed in the form of descriptive qualitative that describe the Analysis of Errors Reflected in Recount Writing Committed by the Tenth Grade Students of SMK Negeri 1 Denpasar. This study aimed at identifying and describing the types and sources of errors. The subjects of this study were the tenth grade students of SMK Negeri 1 Denpasar. The participants of this study were 28 students of class X RPL 1.The data were collected based on the students’ recount writings. There were two techniques to collect the data, namely guided writing and free writing. The errors were classified into 13 types of error as suggested by (Azar, 1999) and (Zawahreh, 2012) namely: singular/plural, word form, verb tense, add a word, omit a word, word order, spelling, punctuation, capitalization, meaning not clear, run-on sentence, preposition, and pronoun. The results of the analysis show there were 307 errors found in Holiday Task 1, 328 errors found in Holiday Task 2, 183 errors were found in Unforgettable Experience Task 1, and 264 errors were found in Unforgettable Experience Task 2. The sources of errors were classified into three types based on the result of student’s writing as suggested by (Richards, 1971) and Brown (1980) namely: Intralingual, Interlingual, and Communication Strategy. The most frequent sources of errors were caused by communication strategy with 587 errors (63%), intralingual with 336 errors (36,51%), and interlingual with 4 errors (0,42%).